Conventional Detection of Resistance of Aedes aegypti Larvae as DHF Vector in Kediri District Against Temephos - Demes Nurmayanti1, Marlik1, Nurhaidah1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dengue Haemorraghic Fever (DHF) becomes health problem in the world. The most number of DHF sufferers in Kediri District in 2016 were in Pare Subdistrict, Ngasem Subdistrict, and Kunjang. However, controlling technique of DHF vector is such as fogging by using active substance of melathion for adult stadium of mosquito and larvasidation by using active substance of temephos for larvae stadium of mosquito. Moreover, resistance of vector against insecticide is global phenomenon, particularly for program management of infectious disease controlling vector and as a singular barrier in the success of vector control chemically. The vector resistance detection can be conducted by using Detection Conventionally through WHO standard method of Susceptibility test in impregnated paper. This research aimed at analyzing detection conventionally the resistance of Aedes aegypti as DHF vector in Kediri District against Malathion and Themepos. This research was True Experiment research and temephos was scattered to the larvae with concentration of 0.01 mg/l, 0.02 mg/l, 0.03 mg/l, and 0.04 mg/l in contact time of 15, 30, 45, and 60 minutes. Data analysis included determination of resistance status by referring to category standard from WHO and analyzing the difference of biota test mortality by using statistical different test of Anova. The result of this research was Aedes aegypti larvae in Kediri District was resistant against temephos with concentration in 0.01 mg/l, 0.02 mg/l, 0.03 mg/l, 0.04 mg/l and there was a significant influence of contact time against the death of Aedes aegypti larvae. Furthermore, suggestion for Health Office in Kediri District was the use of temephos as larvacide was needed in concentration of more than 0.04ml/l. Besides, it was also needed resistance test of Aedes aegypti larvae with concentration of temephos in more than 0.04 mg/l.